Knowledge Work Process: Software Developer’s in Small Medium Enterprise - Mohd Zairol Yusoff; Massudi Mahmuddin; Mazida Ahmad (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Managing knowledge work in the workplace is inherently important and accessible to the organizations for the long terms growth and performance. Software developer is a key successor for the organization success and knowledge work is viewed as the highest complexity of work characteristics. The intentions of software developers to improve the knowledge work process are remain unconsciousness.The paper will address the issue of knowledge work process and try to proposed a method how to improve knowledge work process based on distinct methods and approaches. A literature review was used in order to distinguish the methods and will used data collected 300 respondents from Small Medium Enterprise (SMEs) in Malaysia and also validate the methods by using structural equation modelling. Our results provide evidence on the importance of certain method to improve knowledge work on the software developers and business success, and have implications for both research and practice in the field of SMEs. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7134